2019
DOI: 10.1115/1.4042979
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Considerations for Oil Immersion-Cooled Data Centers

Abstract: The improved efficiency of mineral oil may offer simplicity in facility design compared to traditional air cooling and provide a means for cost savings. Despite its improved cooling efficiency and cost savings, a mineral oil immersion cooling technique is still not widely implemented and original equipment manufacturers are reluctant to jeopardize sales of existing air-based cooling system equipment. Only compelling physics regarding thermal performance of direct immersion cooling is not enough for data center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Liquid immersion is recognized as a viable technological solution to enhance data centre performance usage effectiveness. In this regard, advanced hydro-fluorocarbon liquids 3 (Kawaguchi et al, 2017) and mineral oils (Shah et al, 2019) are reported to have been used. However, the use of these specialized fluids has high costs due to the high cost of fluid acquisition.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Liquid immersion is recognized as a viable technological solution to enhance data centre performance usage effectiveness. In this regard, advanced hydro-fluorocarbon liquids 3 (Kawaguchi et al, 2017) and mineral oils (Shah et al, 2019) are reported to have been used. However, the use of these specialized fluids has high costs due to the high cost of fluid acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…In transitioning from air cooled systems to liquid cooling systems or immersion oil-based cooling systems for data centers, the reliability is an important performance parameter that should be considered. The impact of mineral oil data center cooling on data center reliability receives consideration in (Shah et al 2019). Shah et al (2019) recognize the suitability of using mineral oil-based cooling for server farm operation.…”
mentioning
confidence: 99%
See 3 more Smart Citations